2019
DOI: 10.5946/ce.2019.021
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Eosinophilic Esophagitis Associated with Herpes Esophagitis in a Pediatric Patient

Abstract: Eosinophilic esophagitis is a rare disease in Asian countries, but its incidence is growing rapidly in Western countries. The main pathophysiology of eosinophilic esophagitis is esophageal epithelial barrier dysfunction; disruption of the esophageal epithelial barrier easily induces antigen sensitization to foods and aeroallergens, which leads to subsequent esophageal inflammation as a result of eosinophil recruitment. Here we report a case of an 11-year-old Korean boy who suffered from fever, odynophagia, dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Antigen-presenting cells can induce T helper 2 ( 2) cells leading to eosinophilic infiltration/inflammation of the esophageal lamina propria and submucosa [11]. Also, acute inflammation resulting from HSE can induce predominantly neutrophilic infiltrate, and EoE may be masked if there is an underlying disease [12].…”
Section: Discussionmentioning
confidence: 99%
“…Antigen-presenting cells can induce T helper 2 ( 2) cells leading to eosinophilic infiltration/inflammation of the esophageal lamina propria and submucosa [11]. Also, acute inflammation resulting from HSE can induce predominantly neutrophilic infiltrate, and EoE may be masked if there is an underlying disease [12].…”
Section: Discussionmentioning
confidence: 99%
“…The following keywords were used: “herpes simplex,” “esophagitis,” “immunocompetent,” “child,” and “adolescent.” We included all cases of HE, as defined by the World Health Organization, in immunocompetent adolescents aged between 10 and 19 years. In total, 36 cases were identified [ 4 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]; the clinical characteristics of the patients are shown in Table 1 . The mean age was 15.097 ± 2.736 years, and the male: female ratio was 6.2:1.…”
Section: Discussionmentioning
confidence: 99%
“…We included all cases of HE, as defined by the World Health Organization, in immunocompetent adolescents aged between 10 and 19 years. In total, 36 cases were identified [4,[6][7][8][9][10][11][12][13][14][15][16][17][18]; the clinical characteristics of the patients are shown in Table 1. The mean age was 15.097 ± 2.736 years, and the male: female ratio was 6.2:1.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a series of 5 adult patients with herpes simplex esophagitis had histological and clinical symptoms consistent with the diagnosis of EoE [108]. Kim et al [109] reported an 11-year-old Korean boy suffering from fever, odynophagia, dysphagia, and chest pain. His upper endoscopic examination of the distal esophagus revealed longitudinal ulcers with volcanic appearance.…”
Section: Comorbid Conditionsmentioning
confidence: 99%